(untitled) (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted to develop an 1PM approach for the management of pod borer, Helicoverpa armigera (Hubner) in chickpea field. Out of seven modules studied, module 5 consisting of sequential first spray with Helicoverpa nuclear polyhedrosis viruses (HNPV) @ 500 LE/ha and second spray after seven days interval with Cypermethrin @ 1 ml/ litre gave the best protection with the lowest pod borer damage (4.62%) and provided the highest yield (2096 kg/ha) and maximum net return (Tk. 43746/ha) followed by module 3 where only RNPV was sprayed twice. But the most economic module for pod borer management was M2 where chickpea intercropped with mustard was sown on 15 November. For best protection against pod borer, the most effective 1PM module was chickpea sown on 15 November and first spraying with HNPV @ 500 LE/ha just at 100% plant pod formation stage and second spray after 7 days with Cermethrin @ 1 ml/L, ensuring higher yield and return. Keywords: Integrated management; pod borer; chickpea. DOI: 10.3329/bjar.v35i2.5882 Bangladesh J. Agril. Res. 35(2) : 201-206, June 2010